RFID security - Thornton, Frank; Haines, Brad.; Das, Anand M.; Bhargava, Hersh; Campbell, Anita; Kleinschmidt, John. (Rockland, MA : Syngress Pub., 2006)
RFID is a method of remotely storing and receiving data using devices called RFID tags. RFID tags can be small adhesive stickers containing antennas that receive and respond to transmissions from RFID transmitters. RFID tags are used to identify and track everything from food, dogs, beer kegs to library books. RFID tags use a standard that has already been hacked by several researchers. RFID Security discusses the motives for someone wanting to hack an RFID system and shows how to protect systems. Coverage includes: security breaches for monetary gain (hacking a shops RFID system would allow a.
Chapter 1: What is RFID? -- Chapter 2: RFID Use Cases -- Chapter 3: RFID Processes -- Chapter 4: Threat Modeling for RFID Systems -- Chapter 5: Target Identification -- Chapter 6: RFID Processes -- Chapter 7: Tag Encoding Attacks -- Chapter 8: Tag Application Attacks -- Chapter 9: Attacking the Air Interface -- Chapter 10: Attacking Middleware Communications Chapter 11: Attacking the Directory -- Chapter 12: The Four Disciplines -- Chapter 13: Vulnerability Management -- Chapter 14: Identity Management in RFID -- Chapter 15: Trust Management -- Chapter 16: Threat Management.
Includes index.
Includes bibliographical references and index.
Keywords: Data transmission systems; Radio frequency; Electronic books